The Utilization of Audio Media on Rhythmic Movement Applications in Elementary School - Nugraha, Salsabila Rahmadani; Arie Rakhman; Rahmadi (UNIB Press, 2025)
This research aims to analyze the effectiveness of using audio media in rhythmical movement learning for 6th-grade students at State Elementary School 1 Guntung Manggis. The study uses a descriptive quantitative approach with instruments consisting of knowledge questionnaires and rhythmic movement skill assessment sheets. The results indicate a variation in students' abilities across several key aspects. In the self-assessment aspect, 50% of students fall into the very high category, making it the highest percentage among all measured aspects. In the movement coordination aspect, only 30% of students are in the very high category, whereas 40% of students are in the low category, indicating ongoing challenges in developing motor skills. For the aspect of rhythm accuracy, 33% of students are in the high category and 27% in the very high category, while 23% of students are in the insufficient category and 17% in the very insufficient category. Meanwhile, in the aspect of understanding movement concepts, the majority of students showed good results, with 37% in the very high category and 33% in the high category. These findings indicate that the use of audio media is effective in improving students' understanding and creativity, particularly in the aspects of self-assessment and understanding movement concepts. However, the aspects of movement coordination and rhythm accuracy still require more varied learning strategies and continuous practice so that students' learning outcomes can be more optimal and equitable across all aspects.